Liquidity Risk Management of Islamic Banks in Bangladesh - Zaman, Shafir; Chowdhury, Md Mohiuddin (International Journal of Islamic Business and Economics (IJIBEC), 2019)
Non-performing investment are the amounts that can not be collected by organization from clients. In Bangladesh banking sector is facing severe consequences from lack of collection of non- performing loan(non performing investment for Islamic banks).Emphasizing the significance of the subject the study is undertaken to find out how non performing investment effect performance of Islamic banks in Bangladesh for five year period from 2012 to 2016.Statistical tests such as (descriptive statistics, correlation and regression analysis) are performed to find out the effect non performing investment have on the overall performance of Islamic banks. Correlation analysis opine negative association of non performing investment with bank performance, bank size and capital adequacy ratio. On the other hand, regression analysis did not found any significant effect of non performing investment with bank performance.